Assessment of developmental outcome in very low birth weight infants in Southern Africa using the Bayley Scales of Infant Development (III). Issue 1 (21st August 2017) - Ballot, Daynia Elizabeth; Ramdin, Tanusha; Rakotsoane, David; Agaba, Faustine; Chirwa, Tobias; Davies, Victor Alan; Cooper, Peter Alan
Abstract : Objectives: The study aimed to compare the developmental outcome of very low birth weight infants with a group of normal-term controls in a tertiary hospital in sub-Saharan Africa. Design: A group of 105 very low birth weight infants were assessed at a mean age of 17.6 months (95% CI 16.7 to 18.6) using the Bayley Scales of Infant Development, Third Edition, and compared with a group of normal-term controls at the same mean age. Results: Seven of the study infants (7%) had developmental delay (a score below 70), compared with none in the control group (p=0.04). Three of the seven study infants were delayed on all three subscales, one of whom had cerebral palsy. A further 34% of the study infants were 'at risk' of developmental delay (a score below 85). There was no difference in the mean composite score between the study group and controls for the cognitive (p=0.56), motor (p=0.57) or language (p=0.66) subscales. There was no difference in mean composite scores on all subscales between infants who were appropriate for gestational age and those who were small for gestational age. Cognitive and motor scores remained stable in paired assessments of study infants before and after 1 year of age; language scores decreased significantly (p<0.001). Mechanical ventilation was the only risk factor significantly associated with a cognitive score below 85 in study infants. Conclusion: Very low birth weight infants in sub-Saharan Africa are at risk of developmental delay and require long-term neurodevelopmental follow-up.